Daily field checking list by Walter Rosene, May 29, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 29, 1932. This checklist was used by Walter Rosene to record birds sighted around Boone County with Bob Walker between 6:30 and 11:00, and 1:00 and 5:00. Plustek--flatbed